Biological Control of Foot Rot Disease of Rice Using Fermented Products of Compost and Vermicompost - Manandhar, T; Yami, KD (Scientific World, 2010)
Field trial experiment was conducted at the premise of Nepal Academy of Science and Technology during rainy season (April-June) in 2004 under the rainfed condition. In this study, four types of compost tea: aerated vermicompost tea (ACTV), non aerated vermicompost tea (NCTV), aerated compost tea (ACTC) and non aerated compost tea (NCTV) was prepared and investigated for the suppression of Foot rot disease of Rice caused by Fusarium moniliforme Sheldon - Gibberella fujikuroi. The result was compared with carbendazium (2.5 g per kg dry seeds) treatment and water check. And data was analyzed using one way ANOVA. Among these four compost tea, ACTV showed statistically significant maximum control (25.6% increment of healthy seedlings), followed by ACTC (22.4% increment of healthy seedlings). Least effect was obtained by NCTC (13.6% increment of healthy seedlings). It was observed that 18% of collected Khumal-4 variety rice was infected with Fusarium monoliforme as revealed by Standard Moist Blotter Technique. In concurrence with field trial experiment, treatment of the rice seeds in the Standard Blotter Technique with compost tea revealed highest efficiency of ACTV in reducing the number of affected seeds (12% reduction in affected seeds) followed by ACTC (10% reduction) and NCTV (8% reduction). NCTC were found to be least effective (6% reduction) among the four types of compost tea. Application of compost tea also increases the percentage of germination of seeds, with maximum effect obtained by ACTV (98%). Keywords: Compost tea; Vermicompost tea; Foot rot; Fusarium moniliforme. DOI: 10.3126/sw.v6i6.2634 Scientific World, Vol. 6, No. 6, July 2008 52-57